Single-Seed Casting Large-Size Monocrystalline Silicon for High-Efficiency and Low-Cost Solar Cells. (September 2015) - Gao, Bing; Nakano, Satoshi; Harada, Hirofumi; Miyamura, Yoshiji; Sekiguchi, Takashi; Kakimoto, Koichi
ABSTRACT: To grow high-quality and large-size monocrystal-line silicon at low cost, we proposed a single-seed casting technique. To realize this technique, two challenges—polycrystalline nucleation on the crucible wall and dislocation multiplication inside the crystal—needed to be addressed. Numerical analysis was used to develop solutions for these challenges. Based on an optimized furnace structure and operating conditions from numerical analysis, experiments were performed to grow monocrystalline silicon using the single-seed casting technique. The results revealed that this technique is highly superior to the popular high-performance multicrystalline and multiseed casting mono-like techniques.